Laser assisted additive manufacturing of continuous fiber reinforced thermoplastic composites. (5th October 2017) - Parandoush, Pedram; Tucker, Levi; Zhou, Chi; Lin, Dong
Abstract: Herein, we proposed a novel laser assisted additive manufacturing (AM) methodology that utilizes prepreg composites (glass fiber-polypropylene) with continuous fiber reinforcement to fabricate 3D objects by implementing laser assisted bonding and laser cutting. The microstructure analysis demonstrated no visible void content and excellent interfacial bonding. The bonding strength of the proposed method was evaluated through lap shear strength and peel strength testing; resulting in 50% higher peel strength than hot compaction method, with lap shear strength up to 96% of compression molding benchmark data. Tensile properties of components printed by our method were superior to those of fused deposition modeling (FDM) printed short fiber composites with 300% and 150% of increase in tensile strength and modulus, respectively. Tensile strength of our printed components was comparable to compression molding and stamping, however, tensile modulus was 50% lower in average. Flexural strength of the laser assisted AM parts was also in the range of stamping and compression molding methods, with flexural modulus up to 100% higher than these methods. Overall, our proposed new technique offers an alternative direction in AM of continuous fiber reinforced thermoplastic polymer composites to solve the issues associated with current techniques. Graphical abstract: Highlights: A new laser assisted additive manufacturing (AM) technique was proposed for Continuous fiber reinforced thermoplastic polymer composites (CFRTPCs). The interfacial bonding was excellent with no visible void content. Mechanical properties of the 3D objects were comparable with traditional composite manufacturing methods.